Assessment of Biosafety and Biosecurity Aspects in Diagnostic Clinical Laboratories in Tripoli, Libya - Ben Ashur A1, Abdulwahed E1, Magrahi H1, Elyounsi N1, Annajar B2 (AlQalam Journal of Medical and Applied Sciences, 2017)
Background: Biosafety and Biosecurity are fundamental practices in the laboratory settings, especially, in developing countries, where standard operating procedures (SOPs) are generally low. Objective: To assess the situation and examine policies and standards that laboratories apply to ensure biosafety and biosecurity in their settings, and to eventually come up with number of recommendations on how to implement biosafety and biosecurity procedures. Methods: The study was conducted during the period from November, 2016 to April, 2017 in 10 public hospital laboratories and 25 private diagnostic laboratories in Tripoli, Libya. Results: The results in this study found that 64.8 % of laboratory technicians have used gloves and lab coats and only 30.6% of participants had their recommended vaccines. In addition, accidents during specimen centrifugation were observed in 81% of all laboratories surveyed. Furthermore, separate bins for sharps, procedures for disposal of liquid biological wastes, appropriate chemical waste containers, and appropriate methods (i.e. autoclaving, chemical etc.) to decontaminate all biological culture media were not observed in 77.6%, 82.1%, 46%, and 56.1% respectively, of all audited laboratories. Moreover, presence of biohazard signs on door entrances, written standard basic operating procedures (SOPs), biosafety cabinets, programs for medical surveillance, accident records and biosafety training were not available in 85.7%, 56.1%, 79.1%, 80.1%, 82.6%, 88.3%, respectively, of all laboratories surveyed. Conclusion: This study concluded that the level of biosafety and biosecurity measures in all laboratories surveyed were noticeably low. Moreover, the awareness of laboratory staff and technicians to proper laboratory practices was not generally predominant..